Nuclear matter in different phases and transitions: proceedings of the Workshop Nuclear Matter in Different Phases and Transitions, March 31 - April 10, 1998, Les Houches, France - Campi, Xavier; Płoszajczak, Marek; Blaizot, Jean-Paul (Fundamental theories of physics, 1999)
The Workshop on Nuclear Matter in Different Phases and Transitions, held March 31 - April 10, 1998, brought together both theorists and experimentalists working on the properties of nuclear and hadronic matter produced in heavy-ion collisions in various energy ranges. The main focus was on experimental signals revealing the possible phase changes of the matter, taking into account the finite size of the system, and the non- equilibrium features of the observed phenomena. A discussion of phase transitions in other small quantum systems, such as metallic clusters, or atomic Bose-Einstein condensates was also presented. The papers included in this volume present and review in an understandable and inspiring way the major experimental and theoretical advances in those different communities of physicists addressing similar physics questions, facing similar problems and often using analogous techniques. Audience: This volume will be of interest to postgraduate students and researchers whose work involves nuclear physics, atomic and molecular physics, condensed matter physics, statistical physics, thermodynamics or particle physics
Keywords: Konferenzschrift -- 1998 -- Les Houches; Kernmaterie; Nichtgleichgewichts-Phasenübergang; Phasenumwandlung; Kernanregung